Test-retest reliability and reproducibility of laser- versus contact-displacement sensors in mechanomyography: Implications for musculoskeletal research - Seidl, L.; Tosovic, D.; Brown, J. M. (Journal of Applied Biomechanics, 2017)
Whole muscle mechanomyography (MMG) has gained considerable interest in recent years for its ability to noninvasively determine muscle contractile properties (ie, contraction time [Tc], half-relaxation time [1/2Tr], and maximal displacement [Dmax)]). The aim of this study was to evaluate the test-retest reliability of two fairly novel MMG transducers: a laser-displacement sensor (LDS) and contact-displacement sensor (CDS). MMG was conducted on the rectus femoris muscle of 30 healthy individuals on 4 separate occasions. Test-retest reliability was quantified using intraclass correlation coefficients (ICCs). Both sensors were reliable for time-derived parameters Tc (ICCs, 0.85-0.88) and 1/2Tr (0.77-0.89), with Dmax identified as the most reproducible parameter (0.89-0.94). The 2 sensors produced similar Tc and Dmax measures, although significant (P < .05) systematic bias was identified with the CDS recording higher mean values, on average. However, these differences may not be considered clinically significant. The wide limits of agreement identified between 1/2Tr measures (-19.0 ms and 25.2 ms) are considered unreliable from a clinical perspective. Overall, MMG demonstrated good-to-excellent reliability for the assessment of muscle contractile properties with no significant differences identified between sessions, thus further validating its applicability as a noninvasive measure of muscle contractile properties. ABSTRACT FROM AUTHOR